Good Governance for Efficient Public Services Responsive and Transparent - Ni Putu Tirka Widanti (HK-Publishing, 2022)
AbstractThe provision of goods, services, and administrative services by public service providers is one example of how the implementation of public services by the state is an attempt to meet the fundamental requirements and uphold the civil rights of all citizens. A conceptual framework for improving the ideology, paradigm, culture, and management of a government in order to achieve high performance is called